2017
DOI: 10.1007/s13204-017-0614-7
|View full text |Cite
|
Sign up to set email alerts
|

Controlling conducting channels of single-walled carbon nanotube array with atomic force microscopy

Abstract: In this paper, we report a technique of controlling the number of single-walled carbon nanotubes (SWNTs) between two electrodes. The SWNT devices consist of an array of SWNTs between two silver/palladium electrodes, which are fabricated with electron beam lithography and silver. Using the tip-sample interaction in contact mode of atomic force microscopy (AFM), the number of individual SWNTs can be controllably decreased. The current-voltage measurements indicate that the resistance increases when the conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[3d] Another application is shown in Figure A(iii) and (iv). Nshimiyimana et al reported a technique to use AFM manipulation to modulate conducting channels of CNT‐based electronics device . For carbon‐based electronics, the contact between carbon nanomaterial and electrodes is very important for their performance.…”
Section: Engineering Of Cnts and Graphene For Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3d] Another application is shown in Figure A(iii) and (iv). Nshimiyimana et al reported a technique to use AFM manipulation to modulate conducting channels of CNT‐based electronics device . For carbon‐based electronics, the contact between carbon nanomaterial and electrodes is very important for their performance.…”
Section: Engineering Of Cnts and Graphene For Devicesmentioning
confidence: 99%
“…(iv) CNTs after contact mode AFM manipulation. A‐iii,iv) Reproduced with permission . Copyright 2017, Springer.…”
Section: Engineering Of Cnts and Graphene For Devicesmentioning
confidence: 99%